DEVELOPMENT OF TEACHING MATERIALS OF PARABOLA MOTION USING TRACKER SOFTWARE FOR PHYSICS LEARNING DURING THE COVID-19 PANDEMIC - Sugiono Sugiono (ScienceEdu, 2021)
One of the problems in online learning during the COVID-19 pandemic is monotonous learning. This fact requires teachers to be able creating joy learning. Not only focusing on the knowledge aspect, but also the skill aspect through experiment from home by using technology. So that students feel happy and motivated to learn, able to prove the concepts in real-life, so physics can be understood contextually. One of the software that can be used for distance learning based on physics experiment is tracker. According the facts, the researchers try to develop the learning materials topics parabolic motion using tracker. The research method in this research using 4D model (Define, Design, Development, Disseminate) of Thiargarajan. From the results of the reserach, it can be concluded that, (1) video analysis of parabolic motion using tracker can be getting appropriate results. (2) the results of the design of learning materials for parabolic motion materials include: title, learning instructions, learning objectives, parabolic motion materials, and questions based on critical thinking indicators of interpretation, analysis, evaluation and inference.